O Serviço Social e a exclusão/inclusão social dos portadores de HIV/AIDS :demandas e desafios nos hospitais públicos - Santos, Regina Maria dos (2005)
This research presents the labors developed by the Social Service unto socially excluded HIV/Aids positives at public hospitals in Rio Grande do Norte (RN). It purposes to identify and to analyze the demands brought by the holder onto the Social Service professional as well as the challenges the latter face to minister to the former. It privileges, from the methodological viewpoint, the qualitative and quantitative analysis with the application of questionnaires, direct observation, semi-structured interviews and bibliographic references. Data were collected from 12 (twelve) social assistants who work at Giselda Trigueiro Hospital in Natal (7) and Rafael Fernandes Hospital in Mossoró (5). The central hypothesis that guided this study is that the social inclusion/exclusion process experienced by the HIV/Aids positive on society implies a demand for the Social Service that is inserted in the public health context (specially in HIV-referred public hospitals), whose agents, however, when attempting to answer those demands, meet obstacles due to both the precariousness of public health services and the social complexity that concerns the HIV/Aids epidemic. Results point out that, de facto, the HIV/Aids epidemic, because of the social exclusion/inclusion process to which the holder is subject results a demand for the social agents at hospitals. Demands rise principally from the patient s life condition, considering the increasing pauperization in the epidemic context. As to what it is concerned, social assistants, responding to the needs, come across concrete twofold challenges: the illness in itself, for all social, negative aspects that make part of quotidian life of holders; and the precarious state of the public health service in RN State, since that working conditions are unsatisfactory